Prevention of Transnational Environmental Crime Under Convention on Protection of Environment Through Criminal Law: Agenda and Implementation - M.Z.M. Nomani, Faizanur Rahman, Zubair Ahmed, Tarique Faiyaz, Saif A.Khan, Alaa Hussein Jasim (International Journal of Advanced Science and Technology, 2020)
The environment protection through criminal law instrument combines salient features of civil, tortuous and criminal liability in domestic and international jurisdiction. The gravity environmental pollution and their deleterious impact has given rise to territorial and extra territorial application of general principles of international law along with the criminal and pecuniary sanctions, reinstatement of the environment and corporate  environment liability. The foundation of such a deterrent law was laid down in Principles 13 of Rio Declarations, 1992 which ordains for the development of national liability and compensation law for the pollution induced victims and environmental damage within territorial and extra territorial jurisdictions. The adoption of precautionary principle under Principle 15 of the Rio Declaration, 1992 mandated for evolution of cost-effective measures to prevent environmental degradation and irreversible damages. Therefore it was thought necessary that the legal consequences for environmental offences are to be controlled by sanctioning regimes. The Convention on the Protection of the Environment through Criminal Law, 1998 is a landmark in this direction. The Convention endeavours to develop a framework law for sanctioning regime of environmental criminality in global, regional and national context.  The paper is devoted to critical analysis of its applicability and feasibility in domestic and international community.